1998
DOI: 10.1021/la9802015
|View full text |Cite
|
Sign up to set email alerts
|

Micellar Catalysis in the Nitrosation of Benzoylacetone in an Acid Medium

Abstract: The nitrosation reaction of benzoylacetone (1-phenyl-1,3-butadione) by nitrous acid in an aqueous acid medium is studied in the presence of anionic and cationic micelles. The reaction involves enolization of the ketone, followed by electrophilic nitrosation of the enol. The presence of micelles strongly modifies the keto−enol equilibrium of β-dicarbonyl compounds, like benzoylacetone, in such a way that the enol percentage increases with the surfactant concentration. The increasing enol amount with surfactant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…It is hown that the order Br - > Cl - > SCN - is only applicable when the nucleophile is deactivated by hydration, whereas the “natural” order of nucleophilicity SCN - > Br - > Cl - is observed in solvents such as acetonitrile, acetone, etc or acetonitrile−water mixtures and also for the nitrosation in the micellar phase …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hown that the order Br - > Cl - > SCN - is only applicable when the nucleophile is deactivated by hydration, whereas the “natural” order of nucleophilicity SCN - > Br - > Cl - is observed in solvents such as acetonitrile, acetone, etc or acetonitrile−water mixtures and also for the nitrosation in the micellar phase …”
Section: Resultsmentioning
confidence: 99%
“…In previous works, we have shown that the study of the influence of micellar solutions on the absorption spectrum of β-dicarbonyl compounds, like benzoylacetone, can provide a new method for determining keto−enol equilibrium constants of β-dicarbonyl compounds in water. , As a consequence of the perturbation of the keto−enol equilibrium of benzoylacetone (BZA) brought on by the presence of micelles, the nitrosation reaction of BZA in aqueous acid micellar solutions is greatly modified . In the present study, we investigate the effects of β-cyclodextrin (β-CD) on the keto−enol equilibrium of BZA and dibenzoylmethane (DBM) and on the nitrosation reaction of the enol of BZA, DBM, and acetylacetone (AcAc) in aqueous acid medium.…”
Section: Introductionmentioning
confidence: 95%
“…The nitrosation of monoketones as well as β-diketones, β-ketoesters, and other related structures to give usually the corresponding oximes is nowadays a well-known process. The reaction proceeds via the enol tautomer, but either the enolization or the reaction of the enol can be rate-limiting, depending on the relative rates of enolization and nitrosation of the enol and also on the enol content. For the more acidic enols, a reaction pathway via the enolate anion is also possible and in some cases has been detected. , …”
Section: Introductionmentioning
confidence: 99%
“…By contrast, when the two reagents bind to micelles, k o increases with the surfactant concentration and reaches a constant value when the surfactant counterions are not inert. [20][21][22] With inert counterions, and on the basis of the original assumption that a substrate in one micelle does not react with a reactant in another and that equilibrium is maintained between aqueous and micellar pseudo-phases, rate maxima are observed as a consequence of the dilution of the reagents in the micellar interface at high micelle concentration. 23,24 This is the situation of the buffer-catalyzed tautomerization in TTABr micellar solutions or the H + catalyzed tautomerization in SDS micelles.…”
Section: Concentration Effectsmentioning
confidence: 99%